Effects of different high pressure steaming processes on sensory properties, water-binding capacity, antioxidant and aroma compounds of Ipomoea batatas (L.) Lam - Cao, Anqi; Yang, Mingyi; Hu, Chaofan; Abdelshafy, Asem M.; Bao, Jicheng; Yan, Sining; Lu, Guoquan; Guan, Yuge; Cheng, Jiyu; Pang, Linjiang; Lu, Xinghua (Frontiers in Nutrition, 2025)
BackgroundHigh pressure steaming is a convenient and household cooking method to heat the food evenly and retain original nutrition. This study explored the effects of high pressure steaming processes on the sensory properties, nutritional value, phenolic compounds, water status, and volatile compounds of sweet potato “Xinxiang” and “Pushu32.”ResultsCompared with soft and exquisite “Pushu32”, chewy “Xinxiang” possessed a significantly lower fiber score and exhibited greater changes in adhesiveness, cohesiveness, chewiness, and gumminess after steaming. Sensory evaluation revealed the optimal steaming conditions were 125°C (232.1 kPa) × 15 min for “Xinxiang”, and 115°C (169.1 kPa) × 25 min for “Pushu32”. Low-field nuclear magnetic resonance uncovered that more than 90% of water in sweet potato was immobilized water, and 125°C steaming enhanced bound water proportion, which might contribute to the adhesive texture. The treatment at 125°C for 15 min showed higher anthocyanin, soluble sugar contents, and lower ascorbic acid content in sweet potato. Moreover, 75 volatile components were identified in steamed sweet potato using GC–MS. Correlation analysis implied that benzeneacetaldehyde, trans-β-ionone, α-gurjunene, and nonanal were pivotal aroma compounds of steamed sweet potato. The trans-β-ionone, nonanal, and decanal might be correlated with the dull color of sweet potato. The presence of polyphenols might be conducive to α-gurjunene production and wood aroma.ConclusionThe present study offered the optimal high pressure steaming process for sweet potato and provided new insights into the sensory quality formation and personalized control.